Base Excision Repair and Lesion-Dependent Subpathways for Repair of Oxidative DNA Damage - Svilar, David (Mary Ann Liebert, Inc., 2011)
Nuclear and mitochondrial genomes are under continuous assault by a combination of environmentally and endogenously derived reactive oxygen species, inducing the formation and accumulation of mutagenic, toxic, and/or genome-destabilizing DNA lesions. Failure to resolve these lesions through one or more DNA-repair processes is associated with genome instability, mitochondrial dysfunction, neurodegeneration, inflammation, aging, and cancer, emphasizing the importance of characterizing the pathways and proteins involved in the repair of oxidative DNA damage. This review focuses on the repair of oxidative damage–induced lesions in nuclear and mitochondrial DNA mediated by the base excision repair (BER) pathway in mammalian cells. We discuss the multiple BER subpathways that are initiated by one of 11 different DNA glycosylases of three subtypes: (a) bifunctional with an associated β-lyase activity; (b) monofunctional; and (c) bifunctional with an associated β,δ-lyase activity. These three subtypes of DNA glycosylases all initiate BER but yield different chemical intermediates and hence different BER complexes to complete repair. Additionally, we briefly summarize alternate repair events mediated by BER proteins and the role of BER in the repair of mitochondrial DNA damage induced by ROS. Finally, we discuss the relation of BER and oxidative DNA damage in the onset of human disease. Antioxid. Redox Signal. 14, 2491–2507.